2019
DOI: 10.1002/prp2.547
|View full text |Cite
|
Sign up to set email alerts
|

MrgX2 is a promiscuous receptor for basic peptides causing mast cell pseudo‐allergic and anaphylactoid reactions

Abstract: Activation of MrgX2, an orphan G protein‐coupled receptor expressed on mast cells, leads to degranulation and histamine release. Human MrgX2 binds promiscuously to structurally diverse peptides and small molecules that tend to have basic properties (basic secretagogues), resulting in acute histamine‐like adverse drug reactions of injected therapeutic agents. We set out to identify MrgX2 orthologues from other mammalian species used in nonclinical stages of drug development. Previously, the only known orthologu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 33 publications
1
36
0
Order By: Relevance
“…Consistent with their research 24 , we also confirmed that compound 48/80 activated MRGPRX2, but not MRGPRD, F, and G, suggesting that dog MRGPRX2 expressed in canine CTMC is the functional orthologue of human MRGPRX2. In human MRGPRX2-expressing cells, the EC 50 of certain drugs, such as compound 48/80, somewhat varied among the facilities 11,12,24 . This might have resulted from the difference in the host cells used, transfection methods, and co-expressed Gα proteins.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with their research 24 , we also confirmed that compound 48/80 activated MRGPRX2, but not MRGPRD, F, and G, suggesting that dog MRGPRX2 expressed in canine CTMC is the functional orthologue of human MRGPRX2. In human MRGPRX2-expressing cells, the EC 50 of certain drugs, such as compound 48/80, somewhat varied among the facilities 11,12,24 . This might have resulted from the difference in the host cells used, transfection methods, and co-expressed Gα proteins.…”
Section: Discussionsupporting
confidence: 91%
“…More recently, Grimes et al reported that compound 48/80 and several types of peptides activated dog MRGPRX2 24 . Consistent with their research 24 , we also confirmed that compound 48/80 activated MRGPRX2, but not MRGPRD, F, and G, suggesting that dog MRGPRX2 expressed in canine CTMC is the functional orthologue of human MRGPRX2. In human MRGPRX2-expressing cells, the EC 50 of certain drugs, such as compound 48/80, somewhat varied among the facilities 11,12,24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human MRGPRX2 (mouse orthologue MrgprB2) is a Class A orphan GPCR expressed on primates' mast cells [16]. Human MRGPRX2 binds promiscuously to structurally diverse peptides and small molecules that tend to have basic properties (basic secretagogues), resulting in acute histamine-like adverse drug reactions [35].…”
Section: Discussionmentioning
confidence: 99%
“…This receptor is expressed on connective tissue-type mast cells in the skin (5) and lungs (6). Interestingly, unlike other GPCRs, MRGPRX2 binds to multiple ligands and is potently activated by small cationic molecules and peptides that have amphipathic properties; therefore, this receptor can elicit responses to a wide variety of endogenous and exogenous ligands (7,8). As a result, MRGPRX2 is responsible for mediating mast cell anaphylactic and pseudo-allergic reactions to several US Food and Drug Administration (FDA)-approved drugs (3,(9)(10)(11)(12)(13)(14) and has been implicated in the pathology of chronic inflammatory diseases such as asthma (6), rosacea (15), and urticaria (5).…”
Section: Introductionmentioning
confidence: 99%